2020
DOI: 10.1038/s41467-020-16596-9
|View full text |Cite
|
Sign up to set email alerts
|

Durable and controlled depletion of neutrophils in mice

Abstract: Neutrophils are an essential part of the innate immune system. To study their importance, experimental studies often aim to deplete these cells, generally by injecting anti-Ly6G or anti-Gr1 antibodies. However, these approaches are only partially effective, transient or lack specificity. Here we report that neutrophils remaining after anti-Ly6G treatment are newly derived from the bone marrow, instead of depletion escapees. Mechanistically, newly generated, circulating neutrophils have lower Ly6G membrane expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
202
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(212 citation statements)
references
References 41 publications
8
202
1
1
Order By: Relevance
“…Indeed, we found that treatment of HFD-fed mice with anti-Gr-1 for two weeks only slightly reduced circulating neutrophils (data not shown). A recent paper reported that a combination of anti-Ly6G antibody and anti-rat secondary antibody enhanced neutrophil elimination and reduced neutrophil prevalence, resulting in more efficient and specific chronic neutrophil depletion (29). By using this combo treatment protocol, we found that circulating and hepatic neutrophils were reduced by approximately 30% and 20%, respectively ( Fig.…”
Section: Evidence That Hepatocyte Uptake Of Mir-223-enriched Evs Is Pmentioning
confidence: 61%
See 2 more Smart Citations
“…Indeed, we found that treatment of HFD-fed mice with anti-Gr-1 for two weeks only slightly reduced circulating neutrophils (data not shown). A recent paper reported that a combination of anti-Ly6G antibody and anti-rat secondary antibody enhanced neutrophil elimination and reduced neutrophil prevalence, resulting in more efficient and specific chronic neutrophil depletion (29). By using this combo treatment protocol, we found that circulating and hepatic neutrophils were reduced by approximately 30% and 20%, respectively ( Fig.…”
Section: Evidence That Hepatocyte Uptake Of Mir-223-enriched Evs Is Pmentioning
confidence: 61%
“…S3C and S3D). We did not achieve ~80% circulating neutrophil depletion as described in the original paper (29), and it is not clear whether this difference in depletion efficiency was due to our use of HFDfed mice as compared to chow-fed mice used in the original paper (29). The ~30% reduction of circulating neutrophils was paralleled by a similar, ~30% reduction in serum miR-223 levels ( Fig.…”
Section: Evidence That Hepatocyte Uptake Of Mir-223-enriched Evs Is Pmentioning
confidence: 69%
See 1 more Smart Citation
“…Mast cell deficiency or IL-9 blockade, but not application of an anti-Gr-1 antibody in Treg-depleted BALB/c DEREG mice abrogates this phenotype 3 . Our data indicate that Treg control the activation of mast cells in BALB/c mice via regulation of IL-9, while Gr-1 + granulocytes such as neutrophils and eosinophils 13 are dispensable. Despite increased type 2 immune responses in Treg-depleted C57BL/6 mice, the elevation of S .…”
Section: Introductionmentioning
confidence: 71%
“…In our own neutrophil depletion studies, however, we recognize that the reduced M.tb CFU from our neutrophil depletions of LPS mice did not reach statistical significance, possibly because of incomplete depletion of neutrophils in LPS mice. It is accepted that depletion of neutrophils in mice with the 1A8 clone is difficult for a variety of reasons (29). After depletion, the bone marrow generates neutrophils to maintain homeostasis (55) (19,20,53,54,59).…”
Section: Discussionmentioning
confidence: 99%